HUBUNGAN KEBIASAAN MEROKOK DENGAN TERJADINYA COATED TONGUE PADA PEGAWAI NON-AKADEMIK UNIVERSITAS SUMATERA UTARA - melinder kaur (Dentistry e-Journal FKG USU, 2013)
Abstract Smoking is a habit that is often encountered in the community and may locally cause disturbances in the oral cavity such as leukoplakia, stomatitis nicotina, smoker's melanosis, coated tongue, hairy tongue, candidiasis, leukodema, tobacco keratosis, gingivitis, periodontitis, acute ulcerative necrotizing gingivitis and oral cancer. There is a research that reports that coated tongue is the most frequently encountered lesion in smokers which makes up 64%. The purpose of this research was to examine the relationship between cigarette smoking which consists of the type of cigarette smoked, duration of smoking and number of cigarettes smoked per day with the occurrence of coated tongue. This research is an analytic survey which was conducted using a cross sectional approach to study the dynamics of correlation between risk factors and effects which are smoking and the occurrence of coated tongue. This research was conducted at the Biro Rektor of Universitas Sumatera Utara, Indonesia in Medan, during October and November 2012. The number of samples taken were 68 smokers consisting of non-academic personnel of USU. Data on demographic and smoking habit was obtained by direct interviews with subjects while clinical data was obtained by clinical examination of the subjects who met the inclusion criteria. Analysis of data was performed to test the hypothesis by collecting the univariate and bivariate data. The obtained data were analyzed with Chi-Square test statistics. The results of this research shows anrelationship between the type of cigarettes smoked (P = 0.001) and the number of cigarettes smoked per day with the occurrence of coated tongue (P = 0.010). However, there was no correlation between duration of smoking and the occurrence of coated tongue. Out of the 68 personnel that were examined, there were 55 people who have coated tongue (80.88%). In conclusion, there is a significant relationship between smoking and the occurrence of coated tongue but no significant relationship between the duration of smoking and the occurrence of coated tongue. Key Words: Relationship, Smoking, Coated Tongue